American and British Policy towards Cyprus (1968-1974): New Conclusions in Light of New Evidence - Nicolet, Claude (Études helléniques / Hellenic Studies, 2004)
This article deals wirh developments in Cyprus during the critical period of 1968 to 1974. It focuses on the role played by Britain and the United States in shaping events on the political, diplomatic and military fields. Special attention is paid ro the crises of November 1967 and July-August 1974. The author argues that broader interest considerarions of the two countries on the island and in the region, rather than 'betrayal and conspiracy' were the determining factors of thcir positions and actions. The presentarion and analysis of policies and events is carried out in rhe light of evidence thar became available only recently following the declassification of official British and American Documents.